Communication training as a means of professionally important qualities development of future law enforcement officers - Hohol, I. (Problems of Engineer-Pedagogical Education, 2021)
The article states that prospects for Ukrainian law enforcement system integration into the international, in particular European, legal system as well as the increasing public’s demands for Ukrainian law enforcement agencies condition the need to find ways of improving the practical training of future law enforcement officers, including the communication training as a means of developing professionally important qualities of future law enforcement officers. The author highlights that the personal and professional qualities of a law enforcement officer are the basis of their professional competence; to develop their professional competence, it is necessary to know the required standards for a personality of a future law enforcement officer. Considering the peculiarities of the future law enforcement officer’s professional activity and its structure, the author considers and analyses the personal and professional qualities of the specialist in this field. The method of training is considered by the author from the perspective of modern, innovative educational means, allowing to integrate the principles of contextual education into a vocational educational environment, since the training technologies are based on the key principles of game modelling (effect, exercise, association, communication, achievement of expected results, etc.) and they are balanced through the application of traditional and innovative simulation techniques. Considering the specification of law enforcement and professionally important qualities of future law enforcement officer, in order to ensure effective professional interaction and development of professional communicative culture, the author concludes that it is advisable to combine and use the elements of communicative training, sociopsychological and practical-vocational training. Vocational and communication training application at higher educational institutions, which fosters the development of professionally important qualities and the implementation of integrative content in the vocational training of future law enforcement officers, aims to develop strong-willed qualities and communicative tolerance, empathy, communicative and organisational inclinations, self-regulation and communication control of future law enforcement officers.